The temporal dimension of business processes: requirements and challenges - Pereira, José Luís (2019)
The execution of business processes has a temporal dimension, as there is usually a set of time constraints that processes have to comply with. These time constraints may arise from business rules or legal requirements that organisational processes have to fulfil, or are simply the result of the need to optimise their execution in terms of time, and include, among other aspects, the duration of processes, deadlines associated to their activities, etc. Unfortunately, in terms of both process modelling languages and systems used to manage business processes, the support for the time dimension is still very poor. In this paper, we describe the main temporal aspects that need to be considered in the management of business processes. By doing this, we identify the temporal requirements that process modelling languages need to incorporate, in order to be able to specify those aspects, as well as the challenges to translate those aspects to business processes supported by current BPMS.